مسؤولية مسيري مكاتب الصرف - عطاالله خولة; قلبو سارة (جامعة الوادي University of El Oued, 2025)
یستند قیام المسؤولیة الجزائیة للمسیر على توافر مجموعة من الشروط، أبرزها أن یكون مرتكب الفعل یتمتع بصفة المسیر، وأن ترتكب الجریمة ضمن نشاط المكتب، سواء نتجت عن تصرف شخصي خارج حدود سلطته، أو فعل محظور لصالح المكتب، أو من خلال أفعال تابعیه، و مع ذلك فإن هذه المسؤولیة لیست مطلقة، إذ یمكن أن تنتفي في حالات معینة بناء على موانع قانونیة عامة لأسباب الشخصیة أو الخارجیة، أو موانع خاصة كالتفویض أو المصالحة أو التقادم. وقد یقع على عاتق المسیر إلتزامات یؤدي الإخلال بها إلى إرتكاب مخالفات تصنف كجرائم و تؤثر سلبا على المكتب والنظام المالي، مما دفع المشرع إلى تشدید العقوبات في بعض هذه الجرائم، وقد إقتصرنا في الفصل الثاني الدراسة على أربع جرائم محددة: جریمتان تتعلقان بالتسییر، وجریمتان تتعلق بالذمة المالیة، وذلك بالإستناد إلى المادة 91 من القانون النقدي والمصرفي، التي تحلنا بدورها إلى القانون التجاري الذي أنظم أحكام الشركات التجارية، إذ أجاز المشرع من خلالها أن تأسس مكاتب الصرف في شكل شركة. The establishment of a manager's criminal liability is based on the fulfillment of several conditions, the most prominent of which is that the perpetrator must hold the status of a manager, and that the crime must be committed within the scope of the office’s activities whether it results from a personal act exceeding the limits of their authority, a prohibited act carried out for the benefit of the office, or actions committed by their subordinates. However, this liability is not absolute, as it may be excluded in certain cases based on general legal grounds, whether personal or external, or specific grounds such as delegation, settlement, or the statute of limitations. A manager may bear obligations, the breach of which can lead to violations classified as crimes that negatively affect the office and the financial system. This has prompted the legislator to impose stricter penalties for some of these offenses, In the second chapter, our study is limited to four specific crimes: two related to management and two related to financial liability This analysis is based on Article 91 of the Monetary and Banking Law, which refers in turn to the Commercial Law governing commercial companies, Through these provisions, the legislator has permitted exchange offices to be established in the form of companies.
قانون أعمال
Keywords: manger – offices exchange – offices exchange currency – responsibility penal – banking and monetary law.; مسیر، مكاتب الصرف، المسؤولیة الجزائیة، القانون النقدي والمصرفي.